The impact of the temporal sequence of cranial radiotherapy and platin‐based chemotherapy on hearing impairment in pediatric and adolescent CNS and head‐and‐neck cancer patients: A report from the PanCareLIFE consortium - Scobioala, Sergiu; Parfitt, Ross; Matulat, Peter; Byrne, Julianne; Langer, Thorsten; Troschel, Fabian M.; Hesping, Amélie E.; Clemens, Eva; Kaatsch, Peter; Grabow, Desiree; Kaiser, Melanie; Spix, Claudia; et al. (International journal of cancer, 2024)
The impact of the temporal sequence by which cranial radiotherapy (CRT) and platin‐based chemotherapy (PCth) are administered on sensorineural hearing loss (SNHL) in pediatric and adolescent central nervous system (CNS) and head‐and‐neck (HN) cancer patients has not yet been studied in detail. We examined the ototoxic effects of sequentially applied CRT and PCth. This study included children and adolescents with CNS and HN tumors who participated in the multicountry PanCareLIFE (PCL) consortium. Audiological outcomes were compared between patients who received CRT prior to PCth and those who received it afterwards. The incidence, degree and posttreatment progression of SNHL, defined as Muenster classification grade ≥MS2b, were evaluated in 141 patients. One hundred and nineteen patients were included in a time‐to‐onset analysis. Eighty‐eight patients received CRT prior to PCth (Group 1) and 53 patients received PCth before CRT (Group 2). Over a median follow‐up time of 1.6 years, 72.7% of patients in Group 1 experienced SNHL ≥ MS2b compared to 33.9% in Group 2 (P < .01). A time‐to‐onset analysis was performed for 74 patients from Group 1 and 45 patients from Group 2. Median time to hearing loss (HL) ≥ MS2b was 1.2 years in Group 1 and 4.4 years in Group 2 (P < .01). Thus, audiological outcomes were better for patients who received CRT after PCth than before. This finding should be further evaluated and considered within clinical practice in order to minimize hearing loss in children and adolescents with CNS and HN tumors. What's new? Treatment for pediatric central nervous system (CNS) and head and neck (HN) cancers includes a combination of surgery, radiation therapy, and chemotherapy. However, sensorineural hearing loss (SNHL) can arise from the combined action of radiation and chemotherapy. Here, the authors examined whether the sequence of therapies affected the incidence of SNHL. In a study of 119 patients, they found that 73% of patients who received radiation before chemotherapy experienced SNHL compared with 34% of those who received chemotherapy first. However, no studies have yet compared treatment outcomes based on sequence of therapy.